Towards New Organometallic Wires: Tetraruthenium Complexes Bridged by Phenylenevinylene and Vinylpyridine Ligands - Maurer, Jörg; Sarkar, Biprajit; Kaim, Wolfgang; Winter, Rainer F.; Záliš, Stanislav (Chemistry : a European journal, 2007)
The tetranuclear complexes [{(PiPr3)2(CO)ClRu(μ‐CHCHpy)Ru Cl(CO)(PPh3)2}2(μ‐CHCH‐C6H4‐ CHCH‐1,4)] (3 a) and [{(PiPr3)2(CO)ClRu(μ‐CHCHpy)RuCl(CO)(PPh3)2}2(μ‐CHCH‐C6H4‐CHCH‐1,3)] (3 b), which contain vinylpyridine ligands that connect peripheral Ru(PiPr3)2(CO)Cl units to a central divinylphenylene‐bridged diruthenium core, have been prepared and investigated. These complexes, in various oxidation states up to the tetracation level, have been characterized by standard electrochemical and spectroelectrochemical techniques, including IR, UV/Vis/NIR and ESR spectroscopy. A comparison with the results for the vinylpyridine‐bridged dinuclear complex [PiPr3)2(CO)ClRu(μ‐CHCHpy)RuCl(CO)(PPh3)2(CHCHPh)] (6) and the divinylphenylene‐bridged complexes [{(EtOOCpy)(CO)Cl(PPh3)2Ru}2(μ‐CHCH‐C6H4‐CHCH‐1,4)] (8 a) and [{(EtOOCpy)(CO)Cl(PPh3)2Ru}2(μ‐CHCH‐C6H4‐CHCH‐1,3)] (8 b), which represent the outer sections (6) or the inner core (8 a,b) of complexes 3 a,b, and with the mononuclear complex [(EtOOCpy)(CO)(PPh3)2RuCl(CHCHPh)] (7) indicate that every accessible oxidation process is primarily centred on one of the vinyl ligands, with smaller contributions from the metal centres. The experimental results and quantum chemical calculations indicate charge‐ and spin‐delocalization across the central divinylphenylenediruthenium part of 3 a,b or the styrylruthenium unit of 6, but not beyond. The energy gap between the higher lying styryl‐ or divinylphenylenediruthenium‐based and the lower occupied vinylpyridineruthenium‐based orbitals increases in the order 6<3 b<3 a and thus follows the conjugation within the non‐heteroatom‐substituted aromatic vinyl ligand. Ruthenium‐based wires: Di‐ and tetranuclear 4‐vinylpyridine‐bridged styryl‐ and divinylphenyleneruthenium complexes (see picture) were studied experimentally and by quantum chemistry as building blocks for conducting organometallic oligomers. These complexes undergo a series of ligand‐based oxidations with smaller, yet still detectable, contributions from the metal.